RESEARCH CAPABILITY OF PUBLIC SCHOOL TEACHERS: A BASIS FOR RESEARCH CAPABILITY ENHANCEMENT PROGRAM - Tamban, Victoria Elip; Maningas, Ofelia B. (PEOPLE: International Journal of Social Sciences, 2020)
This study aimed to assess the teachers’ research technical writing skills that set as the basis of capability enhancement program that can nurture and produce upright and competent graduates and empowered community, through relevant and sustainable higher professional and technical instruction, research, extension and production services should take part in helping the DepEd teachers as a member of the larger community. Based on the results most of the respondents were 21-30 years old, female, married, and almost 6-15 years in service as public elementary school teachers. Most of them were finished Bachelor’s degree with specialization on Bachelor of Elementary Education (BEEd). Most of them are Teacher I and II, few are Teacher III and Master Teachers. It was also determined that most of them attended 3-6 research seminars.It was also revealed that the teachers were moderately capable in terms of technical writing of completed research. The findings also convened that there is no significant relationship between their profiles and their research capability except from highest educational attainment which shows significant relationship with research capability, therefore the results of analysis is partly upheld. Based on the findings and conclusions the following are the researchers recommendations: the need for intensive seminar/ training write-shop for technical writing of completed research, the teachers needs to be highly capable in writing completed research that can be presented and published, and the researchers also recommended the action plan for the seminar/training write-shop activities, timeframe, expected output, material requirements, and the responsible entity/person.